Human leukocyte antigen-G 3’ untranslated region polymorphisms are associated with asthma severity - Alves, Cinthia C.; Arruda, Luísa K.P.; Oliveira, Fabíola R.; Massaro, Juliana D.; Aquino, Beatriz J.; Paz, Michelle A. [UNESP]; Castelli, Erick C. [UNESP]; Mendes-Junior, Celso T.; Donadi, Eduardo A. (Elsevier, 2018)
Asthma is a genetically complex chronic inflammatory airway disorder, and according to disease pathogenesis, clinical manifestations may vary according to asthma severity. A gene region close to the human leukocyte antigen-G (HLA-G) gene was identified as an independent susceptibility marker for asthma. Considering that the HLA-G immune checkpoint molecule may modulate inflammation, we evaluated the diversity of the HLA-G 3′ untranslated region (3′UTR) in asthmatic patients stratified according to disease severity. We evaluate the entire HLA-G 3′UTR segment in 115 Brazilian patients stratified into mild (n=29), moderate (n=21) and severe asthmatics (n=65), and in 116 healthy individuals. HLA-G 3′UTR typing was performed using Sanger sequencing. The multiple comparisons among patients stratified according to disease severity revealed several associations; however, after Bonferroni's correction, the following results remained significant: i) the +3010C and +3142G alleles were overrepresented in mild asthma patients when compared to controls; ii) the +3010G and +3142C alleles were overrepresented in severe asthma patients in comparison to patients with mild asthma. In conclusion, the +3010C/G and +3142C/G HLA-G 3′UTR variation sites were differentially associated according to asthma severity.
Keywords: Asthma; HLA-G; MHC; Mild asthma; Severe asthma; Susceptibility